2012
DOI: 10.1638/2010-0108r.1
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF RDRIOSTRAIN OFMYCOBACTERIUM TUBERCULOSISIN TAPIRS (TAPIRUS TERRESTRIS) FROM A ZOO IN BRAZIL

Abstract: Tuberculosis is a chronic infection caused by strains of the Mycobacterium tuberculosis complex and occurs in both animal and human populations. The death of a tapir showing purulent material and a hard mass in the lungs at necropsy raised suspicion of a potential disease caused by mycobacteria species in a Brazilian zoo. Later, two other tapirs with similar signs died and were further investigated. Polymerase chain reaction (PCR) from bronco-alveolar lavages was performed, and both animals tested positive for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…http://seer.ufrgs.br/ActaScientiaeVeterinariae clinical and anatomopathological similarities with the infections of a tapir and coati at the zoo of Curitiba, Paraná state [8], and non-human primates in bioteries in Belém, Pará state [4]. In the present case, as in the others previously reported, Mycobacterium tuberculosis complex was detected identified.…”
Section: Cr321supporting
confidence: 79%
See 1 more Smart Citation
“…http://seer.ufrgs.br/ActaScientiaeVeterinariae clinical and anatomopathological similarities with the infections of a tapir and coati at the zoo of Curitiba, Paraná state [8], and non-human primates in bioteries in Belém, Pará state [4]. In the present case, as in the others previously reported, Mycobacterium tuberculosis complex was detected identified.…”
Section: Cr321supporting
confidence: 79%
“…Tuberculosis in a Malayan tapir showed multiple white, caseous nodules measuring from 1 to 5 mm in diameter spread throughout the lungs [2]. The authors did not mention the manifestation of acinar processes; however, the lesions can be generalized and present in the mediastinal lymph nodes and in the liver, spleen, kidneys, ovaries, areas of the serosa, diaphragm, mesenteric lymph nodes, intestines and uterus [8].…”
Section: Cr321mentioning
confidence: 99%
“…Furthermore, there is some reluctance to publicize findings due to public relations impact and loss of revenue (KANEENE et al, 2010). The present study revealed the occurrence of M. tuberculosis complex in Barbary sheep, an exotic species; however, the same Brazilian zoo described in 2006 the first report of RD Rio M. tuberculosis infection in tapirs (MURAKAMI et al, 2012). Not surprisingly, wild animal species are thought to be reservoirs for more than 70% of all emerging infections (KUIKEN et al, 2005;CHOMEL et al, 2007) (MICHEL et al, 2003), antelopes, capuchin and vervet monkeys (MICHEL et al, 2013).…”
mentioning
confidence: 44%
“…Veterinary practitioners regard tapirs to be the indicator species that may help diagnose bovine mycobacterium infection [22,23]. The conducted research showed that the tapirs described in the work did not have a tuberculin skin test done before being transferred to the Silesian zoo.…”
Section: Discussionmentioning
confidence: 99%